Here, we are required to determine the solution to the equation: 13.7y = 6.2y + 30?
The solution to the equation is y = 7.5
The solution is thus,
- 13.7y = 6.2y + 30
- 13.7y - 6.2y = 30
- 7.5y = 30
Therefore, y = 30/7.5 = 4
Therefore, y = 4 is the solution to the equation.
Read more:
brainly.com/question/12184348
The coefficient matrix is build with its rows representing each equation, and its columns representing each variable.
So, you may write the matrix as
![\left[\begin{array}{cc}\text{x-coefficient, 1st equation}&\text{y-coefficient, 1st equation}\\\text{x-coefficient, 2nd equation}&\text{y-coefficient, 2nd equation} \end{array}\right]](https://tex.z-dn.net/?f=%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%5Ctext%7Bx-coefficient%2C%201st%20equation%7D%26%5Ctext%7By-coefficient%2C%201st%20equation%7D%5C%5C%5Ctext%7Bx-coefficient%2C%202nd%20equation%7D%26%5Ctext%7By-coefficient%2C%202nd%20equation%7D%20%5Cend%7Barray%7D%5Cright%5D%20%20)
which means
![\left[\begin{array}{cc}4&-3\\8&-3\end{array}\right]](https://tex.z-dn.net/?f=%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D4%26-3%5C%5C8%26-3%5Cend%7Barray%7D%5Cright%5D%20%20)
The determinant is computed subtracting diagonals:
![\left | \left[ \begin{array}{cc}a&b\\c&d\end{array}\right]\right | = ad-bc](https://tex.z-dn.net/?f=%20%5Cleft%20%7C%20%5Cleft%5B%20%5Cbegin%7Barray%7D%7Bcc%7Da%26b%5C%5Cc%26d%5Cend%7Barray%7D%5Cright%5D%5Cright%20%7C%20%3D%20ad-bc%20)
So, we have
![\left | \left[\begin{array}{cc}4&-3\\8&-3\end{array}\right] \right | = 4(-3) - 8(-3) = -4(-3) = 12](https://tex.z-dn.net/?f=%20%5Cleft%20%7C%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D4%26-3%5C%5C8%26-3%5Cend%7Barray%7D%5Cright%5D%20%5Cright%20%7C%20%3D%204%28-3%29%20-%208%28-3%29%20%3D%20-4%28-3%29%20%3D%2012%20%20)
Answer:
5n + 12
Step-by-step explanation:
Perform the indicated multiplication. Then combine like terms:
2n + 3n + 12 = 5n + 12 (answer)
Answer:
c) 2 + 3 = 5 TRUE
d) 2 + (–3) = -1 True
Step-by-step explanation:
When adding integers (positive and negative whole numbers), there are three cases:
- Positive and positive increases and sum is positive. Ex. 4 + 6 = 10
- Positive and negative where you subtract and take the sign of the larger number. Ex. 3 + -8 = -5 or -3 + 8 = 5
- Negative and negative decrease and the sum if negative. Ex. -4 + -6 = -10.
Use these rules to simplify each expression.
a) 2 + (–3) = -1 not 1 FALSE
b) –3 + 2 = -1 not 5 FALSE
c) 2 + 3 = 5 TRUE
d) 2 + (–3) = -1 True